Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/mao.0000000000001572
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Complications and Surgical Failures After Ossiculoplasty

Abstract: Long-term complications are a significant consideration in all the patients undergoing ossiculoplasty. Our data suggest that tobacco smoking, Eustachian tube dysfunction, and an unexpectedly poor hearing result on the first postoperative audiogram are all important risk factors for the development of significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…Although no material has been clearly demonstrated to yield better results than the others [9,12], a manufactured PORP and TORP are popular options for repairing the ossicular chain. Complications related to ossiculoplasty include the need for subsequent surgery, secondary ventilation tube insertion, displacement of the prosthesis, extensive scar tissue formation, and recurrence of perforation [13]. Tympanoplasty without ossiculoplasty may reduce complications and additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Although no material has been clearly demonstrated to yield better results than the others [9,12], a manufactured PORP and TORP are popular options for repairing the ossicular chain. Complications related to ossiculoplasty include the need for subsequent surgery, secondary ventilation tube insertion, displacement of the prosthesis, extensive scar tissue formation, and recurrence of perforation [13]. Tympanoplasty without ossiculoplasty may reduce complications and additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Worsening word recognition has been seen in patients in other series over long terms, but the reasons for this worsening have had limited discussion. 22,24 While it is difficult to determine the exact cause of this drop for individual patients, in all likelihood, this represents a progression of a sensorineural component of hearing loss present at the time of surgery. It is possible that manipulation of the oval window during surgery expedited this progression, although this cannot be proven definitively.…”
Section: Discussionmentioning
confidence: 99%
“…12 This inconsistency is a reflection of the many variables likely to play a role in ossiculoplasty outcomes, including the underlying middleear pathology, the status of the Eustachian tube, surgical techniques, prostheses design, and patient factors. 4,[13][14][15][16][17][18][19][20][21] Furthermore, published data differ among studies with regard to the studied population, outcome measures reported, and follow-up periods. 22 Most agree, however, that careful patient selection is important in optimizing potential contributing factors and favoring ossiculoplasty outcomes.…”
Section: Discussionmentioning
confidence: 99%